HUBUNGAN PENDIDIKAN DAN KEMISKINAN: PENDEKATAN VARIABEL MEDIASI PENDAPATAN PER KAPITA - Purnomo, Sodik Dwi; Istiqomah, Istiqomah; Suharno, Suharno (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
Previous researches shows that the relationship of education on poverty is negative and significant. Therefore, this study introduces the mediating variable income per capita to analyze the path of education on poverty. Research purposes is analyzing whether per capita income mediates the effect of education on poverty. The data used are secondary data in the Province of the Special Region of Yogyakarta in the period 2000-2018. This research method is path analysis. The results show that per capita income mediates the relationship of education on poverty in partial mediation. This finding implies the importance of improving the quality of human resources through education to reduce poverty.